Ontology-based access to temporal data with Ontop: A framework proposal - Güzel Kalayci, Elem; Brandt, Sebastian; Calvanese, Diego; Ryzhikov, Vladislav; Xiao, Guohui; Zakharyaschev, Michael (Zielona Góra: Uniwersytet Zielonogórski)
Predictive analysis gradually gains importance in industry. For instance, service engineers at Siemens diagnostic centres unveil hidden knowledge in huge amounts of historical sensor data and use it to improve the predictive systems analysing live data. Currently, the analysis is usually done using data-dependent rules that are specific to individual sensors and equipment. This dependence poses significant challenges in rule authoring, reuse, and maintenance by engineers. One solution to this problem is to employ ontology-based data access (OBDA), which provides a conceptual view of data via an ontology. However, classical OBDA systems do not support access to temporal data and reasoning over it.
Keywords: metric temporal logic; ontology-based data access; SPARQL query; Ontop